In Pursuit of Seamless Education Collaboration between Educational Sectors - Miller, Michael T.; Evans, Jennifer P. ([S.l.] : Distributed by ERIC Clearinghouse, 1997)
A study identified potential barriers to successful intra-institutional collaboration involving educators at secondary schools, community colleges, community education agencies, and higher education institutions. Twenty educators from various educational agencies in Alabama and Georgia were identified to be included in the interview process by using a snowball technique. All individual were interviewed in person. Notes were taken during each interview and provided to each participant for amendment, correction, or editing. Analysis of interview notes indicated moderate duplication in many noncredit, nondegree programs. Organizational collaboration was seen as having the ability to enhance the range and depth of courses and to allow for greater organizational flexibility in offering courses. The primary barrier to working with other educational providers was miscommunication among program directors, teachers, and other managers and administrators. These other barriers were identified: pressure to maintain academic freedom and control of the classroom, teachers who preferred to "teach to the test," rapid turn around time in local industry incentive training, tradition, attitude of college professors, energy and incentive for teachers to communicate with colleagues at other providers, the "make-a-buck" attitude in self-supporting programs, and administration of various agencies. (YLB)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Agency Cooperation; Community Colleges; Community Education; Continuing Education; Cooperative Planning; Coordination; Educational Cooperation; Educational Planning; Educational Research; Higher Education; Institutional Cooperation; Interschool Communication; Lifelong Learning; Postsecondary Education; Secondary Education; Teacher Collaboration; Two Year Colleges; Reports, Research